Invested in Prisons: Prison Expansion and Community Development in Canada - Greg McElligott (Studies in Social Justice, 2017)
This paper critically examines the claim made by Canadian Conservative politicians that prison expansion is likely to produce economic gains for Canadian prison towns. Such claims raise many questions about the actual beneficiaries of prison construction, and the depiction of prisons as “infrastructure” serving some public good or even promoting social justice. After reviewing relevant literature from American debates on this topic, I focus on more specific Canadian conditions, and use public tendering data to trace the path of prison spending. The evidence suggests that prison expansion is unlikely to benefit surrounding communities, although interests elsewhere tend to reap major gains.